Analytical and semi-analytical solutions for Phi-four equation through three recent schemes - Khater, Mostafa M.A.; Mousa, A.A.; El-Shorbagy, M.A.; Attia, Raghda A.M. (Results in physics, 2021)
•Solving a mathematical model of reality in the form of waves is at the heart of quantum mechanics.•Employing the nonlinear Phi-four equation.•Applying three recent computational schemes.•Explaining the obtained solutions through some distinct types of sketches. This manuscript investigates the analytical and semi-analytical solutions of nonlinear phi-four (PF) equation by applying the sech–tanh expansion method, modified Ψ′Ψ-expansion method and Adomian decomposition method. This equation is considered as a particular case of the well-known Klein–Fock–Gordon (KFG) equation. The KFG equation is derived by Oskar Klein and Walter Gordon and relates to Schrödinger equation. Many quantum effects can be studied based on the PF model’s solutions, such as wave-particle duality to describe reality in the form of waves is at the heart of quantum mechanics. The considered model is also used to explain de Broglie waves’ character, the spineless relativistic composite particles, relativistic electrons, etc., which are also the main icons for a good understanding of the phenomenon of quantum physics. Through two recent analytical schemes, handling this model gives many novel computational solutions that are tested through the semi-analytical scheme to investigate their accuracy. Demonstrating the obtained analytical and matching between analytical and semi-analytical through some distinct sketches shows the considered model’s novel physical properties.